Molecular epidemiology of carbapenem-resistant Acinetobacter baumannii in Italy - Zarilli, R.; Bagattini, M.; Migliaccio, A.; Esposito, E. P.; Triassi, M. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Carbapenem-resistant (CR) Acinetobacter baumannii has been increasingly recognized as a major cause of health care-associated infections in critically ill patients and hospital outbreaks. Methods. A narrative review of literature was conducted, searching PubMed database for articles on CR Acinetobacter spp. isolates from Italy published between January 2010 and December 2019.  Results. CR A. baumannii isolates assigned to international clonal lineage II (ICL II) and to ST78 clonal lineages were responsible for several epidemics in Italian hospitals during 2002-2018. Molecular analysis of carbapenem resistance showed the presence of OXA-58 CHDL in A. baumannii isolates assigned to ICL II and ST78 clonal lineage, which was replaced by OXA-23 CHDL in A. baumannii isolates assigned to ICL II since 2007 in several hospitals. CR A. baumannii was mainly responsible for respiratory tract infections and at a lesser extent for sepsis in intensive care unit patients.Conclusions. Our data reinforces the need to monitor the molecular epidemiology of CR A. baumannii and its associated antimicrobial resistance genes at national level.